The Effect of Social Network on Partnership Programs and MSMEs Performance - Junaidi Junaidi; Zulkarnain Lubis; Ihsan Effendi (Publikasi Indonesia, 2023)
The goal of this research is to determine the influence of social networks on the partnership program and the performance of SMEs and the role of the partnership program in mediating the social network on the performance of MSMEs. Concerning the study's population, MSMEs assisted at PTPN III, a total of 243 MSMEs business actors were declared successful in MSMEs development. A saturated canoe was used as the sampling method. As a result, the sample size for this study is 243 MSMEs business actors. The information was gathered using a questionnaire tailored to each variable indicator item. Structural Equation Modeling with Amos was used for data analysis. The findings revealed that social network has a significant impact on the partnership program and MSMEs' performance; partnership program has a direct and significant impact on the MSME's performance; partnership program has a significant indirect influence on the performance of MSMEs by mediating social networks.